Application of CAMQL technique on external cylindrical grinding of aisi 4340 steel with CBN grinding wheel - Fragoso, Kamira Miksza [UNESP]; Francelin, Alan Polato [UNESP]; Lopes, José Claudio [UNESP]; Sanchez, Luiz Eduardo de Angelo [UNESP]; de Melo, Hamilton José [UNESP]; Lodi, Alexandre Araujo; Aguiar, Paulo Roberto [UNESP]; Bianchi, Eduardo Carlos [UNESP] (FapUNIFESP (SciELO), 2019)
The grinding process provides us with good surface finish and good dimensional and geometric precision. Also, ground pieces have a high added value due to this process being a finishing one and is commonly carried out in the last stages of manufacture. A limiting factor for grinding is the great amount of heat generated, which is better removed from the cutting zone by the application of cutting fluids. The fluid used, in most of cases, are pollutants and contain substances that are harmful both to workers and environment, besides having a high cost of purchase, maintenance and disposal. In order to reduce the amount of fluid used during grinding, the present work was developed. Its main objective is to improve the technique of minimum quantity of lubrication (MQL) by combining it with the application of compressed cold air. This aims to increase the cooling effect and yet minimize the heat concentration in the cutting zone. To evaluate the effectiveness of the technique, the parameters of roughness, circularity, grinding wheel wear and power consumption during machining were analyzed. These values were measured for three different methods of application of cutting fluids during grinding to compare. The conventional flood application obtained the best results for the parameters analyzed while CAMQL (cold air minimum quantity lubrication) presents intermediate results and MQL (minimum quantity lubrication) the worst results obtained in all analyzed parameters. The proposed technique of reducing the amount of fluid used has generally been positive, proving its feasibility for the grinding of AISI 4340 steel using CBN grinding wheel with CBN being Cubic Boron Nitride, a supera-brasive material.
Aplicação da técnica de CAMQL na retificação cilíndrica externa do aço aisi 4340 utilizando rebolo de CBN
Keywords: AISI 4340 steel; CAMQL; CBN grinding wheel; Cold air; Grinding